2010
DOI: 10.1021/jm101014v
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Activity of Novel 5-((Arylfuran/1H-pyrrol-2-yl)methylene)-2-thioxo-3-(3-(trifluoromethyl)phenyl)thiazolidin-4-ones as HIV-1 Fusion Inhibitors Targeting gp41

Abstract: On the basis of our earlier molecular docking analysis, we designed and synthesized 5-((arylfuran/1H-pyrrol-2-yl)methylene)-2-thioxo-3-(3-(trifluoromethyl)phenyl)thiazolidin-4-ones (12a-o) as HIV-1 entry inhibitors. Compounds 12a-o effectively inhibited infection by both laboratory-adapted and primary HIV-1 strains and blocked HIV-1 mediated cell-cell fusion and gp41 six-helix bundle formation. Molecular docking analyses on two highly active inhibitors, 12b, containing a carboxylic acid group, and 12m, contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 36 publications
(71 reference statements)
1
42
0
Order By: Relevance
“…The synthesis of 2-oxo-3,7-dihydro-2Н-thiopyrano [2,3- (6)(7)(8)(9)(10)(11)(12)(13) 16 , 6-carboxymethylene-2-oxo-3,5,6,7-tetrahydro-2h-…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of 2-oxo-3,7-dihydro-2Н-thiopyrano [2,3- (6)(7)(8)(9)(10)(11)(12)(13) 16 , 6-carboxymethylene-2-oxo-3,5,6,7-tetrahydro-2h-…”
Section: Methodsmentioning
confidence: 99%
“…arylfurans include numerous compounds exhibiting interesting biological and pharmacological activities. [13] For instance, the 2-arylfuran derivative 1 (dantrolene) ( Figure 1) is a muscle relaxant commonly used for the treatment of life-threatening complications during anesthesia; [14] compound 2 ( Figure 1) effectively inhibits infection by both laboratory-adapted and primary HIV-1 strains and blocks HIV-1 mediated cell-cell fusion and gp41 six-helix bundle formation; [15] azofuran 3 ( Figure 1) possesses significant activity against cancer cells without affecting the lymphocyte proliferation in human peripheral blood mononuclear cells; [16] the 3-substituted (5-arylfuran-2-ylcarbonyl)-guanidine 4 ( Figure 1) exhibits high Na + /H + exchange isoform-1 inhibitory activity; [17] and bioymifi (5) (Figure 1) is a compound that binds to the extracellular domain of the DR 5 receptors and induces their aggregation. [18] In 2009, Doucet and co-workers reported that 2-butyl-5-arylfurans could be selectively prepared by the reaction of 2 equiv.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%
“…Further drug-like inhibitors explorations, including the primary identification of NB-2 and NB-64 micromolar leads [325] and docking-guided optimization to derivatives of 2-aryl 5-(4-oxo-3-phenethyl-2-thioxothiazolidinylidenemethyl) furan (Fig. 3c), have been carried out recently by the same group [326,327]. The most potent inhibitors synthesized so far acquired 14nM IC 50 against the formation of gp41.…”
Section: Towards Potent Ppi Inhibitorsmentioning
confidence: 99%